Development of clean renewable fuel from wastewater towards a sustainable energy source using green technology approach: HEC2 - Zularisam, A. W. (Penerbit UMP, 2010)
Fossil fuel such as diesel and petrol that are drawn from finite resources are non renewable and is becoming more expensive and unaffordable besides polluting the environment. There has been a constant increase in oil price due to depletion of fossil fuel resources and increase in energy demand (due to intensive industrialization, population and automotive activities). Furthermore fossil fuel bums incompletely thus contributes to emission of greenhouse gasses, global warming and other detrimental environmental problems. Therefore a cheaper, cleaner, sustainable and environmental friendly fuel source is urgently needed and subsequently an innovative system has been designed and developed in order to overcome the above mentioned problems.